2020
DOI: 10.1186/s13148-020-00826-4
|View full text |Cite
|
Sign up to set email alerts
|

Histone methylation and vascular biology

Abstract: The vasculature not only transports oxygenated blood, metabolites, and waste products but also serves as a conduit for hormonal communication between distant tissues. Therefore, it is important to maintain homeostasis within the vasculature. Recent studies have greatly expanded our understanding of the regulation of vasculature development and vascular-related diseases at the epigenetic level, including by protein posttranslational modifications, DNA methylation, and noncoding RNAs. Integrating epigenetic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 136 publications
(165 reference statements)
0
51
0
2
Order By: Relevance
“…Protein methylation usually occurs on lysine or arginine, and both histones and nonhistone proteins can be methylated [ 104 – 106 ]. A plethora of studies have demonstrated that protein methylation plays an important role in cell survival/death and diseases [ 104 , 107 109 ], but the research on their roles in ferroptosis is in its infancy.…”
Section: Posttranslational Modifications (Ptms) In Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Protein methylation usually occurs on lysine or arginine, and both histones and nonhistone proteins can be methylated [ 104 – 106 ]. A plethora of studies have demonstrated that protein methylation plays an important role in cell survival/death and diseases [ 104 , 107 109 ], but the research on their roles in ferroptosis is in its infancy.…”
Section: Posttranslational Modifications (Ptms) In Ferroptosismentioning
confidence: 99%
“…Protein methylation usually occurs on lysine or arginine, and both histones and nonhistone proteins can be methylated [ 104 – 106 ]. A plethora of studies have demonstrated that protein methylation plays an important role in cell survival/death and diseases [ 104 , 107 109 ], but the research on their roles in ferroptosis is in its infancy. For example, lysine demethylase 3B (KDM3B), a histone H3K9 demethylase, inhibits erastin-induced ferroptosis by cooperating with the transcription factor activating transcription factor 4 (ATF4) to upregulate SLC7A11 expression [ 110 ] ( Figure 4 ).…”
Section: Posttranslational Modifications (Ptms) In Ferroptosismentioning
confidence: 99%
“… 80 Moreover, histone methylation and demethylation have been studied in coronary atherosclerosis widely. 81 …”
Section: Covalent Modificationsmentioning
confidence: 99%
“…It is well known that macromolecule methylation is a feature pertaining to both DNA and proteins [47,48] with special regard to histones. Recently, histone methylation has become a major hotspot for research on both cancer [49] and vascular diseases [50], which are among the leading causes of mortality [51]. In this respect, it has been proposed that (I) methionine-homocysteine modulates the SAM/SAH ratio and therefore the rate of SAM-dependent methylation under pathological conditions and that (II) hypomethylation on frequently modified histones is involved in the deregulation mechanisms of autoimmune and metabolic disorders, as well as in cardiovascular disease.…”
Section: Finding(s) Reference(s)mentioning
confidence: 99%